Knowledge, practices and compliance related to COVID-19 among Nepalese population in Province 2, Nepal - Phoolgen Sah; Ashok Kumar Mandal; Bhuvan Saud; Savan Kumar Yadav; Sanjeet Kumar Sah; Mahasagar Gyawali; Shailendra Kumar Karn (Elsevier, 2022)
Aim: The study aimed to access the knowledge, practice, and compliance related to COVID-19 among people residing in Province 2, Nepal. Materials and methods: A descriptive cross-sectional study was conducted from October 2020 to March 2021. A total of 457 participants of eight districts of Province 2 were enrolled after obtaining consent. Data were collected by face-to-face interviews with participants. A total of 31 validated pre-structured questionnaires were asked to participants in which 11 questions were for knowledge, 12 questions were for practices, and 8 questions were for compliance related to COVID-19. For tool validation, pre-testing was done in 10.0% of individuals of the targeted study population of Mahottari district. Results: Out of 457 participants, 353(77.2%) were male. The majority of the participants were unmarried (68.3%), had only school-level education (26.5%), Hindu by religion (89.7%), farmers (23.0%), and businessmen (23.0%). More than 75.0% of individuals had knowledge about the causative agent of COVID-19 symptoms and the purpose of isolation. About 53.8% of participants had good knowledge of social distancing, 31.1% had knowledge of masks, and 39.3% knew about sanitizer. Moreover, 94.3% of the respondents had good knowledge of hand-washing practice with soap-water and use of sanitizer, 89.1% had good knowledge of wearing masks and 82.9% followed social distancing. Compliance with standard procedures of sneezing was recorded in 43.1%, washing hands with soap water/sanitizer was 82.3%, and disposal of masks was 53.6%. A significant association was observed between gender with knowledge and compliance (p < 0.05). District-wise association with knowledge, practice and compliance was found to be significant (p < 0.05). Conclusion: The findings suggest that participants have a good level of knowledge; however, the practice and compliances are considerably low related to COVID-19.